Isolation and Genomic Characterization of Echovirus 11 from faeces of a Non-Human Primate in Nigeria (2021)
We recently investigated the presence of enteroviruses (EVs) in non-human primates (NHPs) in Northern Nigeria and documented the presence of EV-A76 of South-East Asian ancestry in an NHP. In this study, we go further to ask if we could also find EVs in NHPs indigenous to the forested South-south Nigeria. Fresh faecal samples were collected from the floor of 10 cages housing NHPs in Cross River Nigeria, resuspended in PBS and subjected to RNA extraction, cDNA synthesis, PanEnt 50-UTR and PanEnt VP1 PCR assays. None of the samples was positive for the PanEnt VP1 assay, but one sample was positive for PanEnt 50- UTR PCR. This sample was subsequently inoculated into RD cell line, produced CPE and the isolate analysed by PCR assays, next-generation whole genome sequencing and passage in four different cell lines showing replication in two of them. Analysis of the complete genome of the isolate identified it as an Echovirus 11 (E11) and revealed a recombinant genomic structure. Phylogenetic analysis showed that the E11 NHP strain was related to human clinical isolates suggesting a zoonotic behaviour. We describe the first isolation and complete genome characterization of an E11 obtained from an NHP in Nigeria having zoonotic potential.